Reception games of Dušan Taragel (the non-actor) - Peter Darovec (Slovenska Literatura)
The study focuses on the various forms of a specific postmodernist literary game, whose framework and rules are primarily determined by the conventions of pop culture genres. These genre foundations serve as a substrate for creating a unique artistic expression. The transitional period of the 1990s in Slovak literature, marked by significant changes in the socio-political landscape and a shift in literary life, is identified as the typical era for such ironically subversive text-forming practices. This period also saw a shift in readers’ genre preferences toward popular culture. The article analyses the forms of literary games with genres on the works of contemporary Slovak prose writer Dušan Taragel (1961), drawing on texts spanning his entire oeuvre from his debut book Rozprávky pre neposlušné deti a ich starostlivých rodičov (Stories for naughty children and their caring parents, 1997) to his latest novel Mafiánske balady (Mafia Ballads, 2022). A more extensive interpretation is dedicated to this recent novel, as it serves, in many respects, as a bridge between the present and the author’s creatively productive decade of the 1990s.